ROS-Influenced Regulatory Cross-Talk With Wnt Signaling Pathway During Perinatal Development - Chatterjee, Sharmistha; Sil, Parames C. (Frontiers in Molecular Biosciences, 2022)
Over a century ago, Otto Warburg noticed and measured the rapid burst of oxygen consumption that occurs as life begins in the form of a sea-urchin oocyte. Since then, scientific research has taken strides to establish that Reactive Oxygen Species (ROS), besides being toxic effectors of cellular damage and death, also act as molecular messengers in important developmental signaling cascades, thereby modulating them. Wnt signaling pathway is one such developmental pathway, which has significant effects on growth, proliferation, and differentiation of cells at the earliest embryonic stages of an organism, apart from being significant role-players in the instances of cellular transformation and cancer when this tightly-regulated system encounters aberrations. In this review, we discuss more about the Wnt and ROS signaling pathways, how they function, what roles they play overall in animals, and mostly about how these two major signaling systems cross paths and interplay in mediating major cellular signals and executing the predestined changes during the perinatal condition, in a systematic manner.